A tracheoinnominate artery fistula presenting with massive hemorrhage in a 13-year-old boy - Jung Heon Kim; Jeong-Yong Lee; Hyung-Rae Cho; Jong Seung Lee; Jeong-Min Ryu (Pediatric Emergency Medicine Journal, 2015)
Despite its rarity, a tracheoinnominate artery fistula can result in catastrophic hemorrhage. Here, we describe a case of a 13-year-old boy with such a condition following tracheostomy. After identification of pulsatile bleeding from the tracheostoma, temporary control of hemorrhage was obtained using hyperinflation of the tracheostomy tube cuff. Subsequently, a lesion indicative of a tracheoinnominate artery fistula was found on a computed tomography scan, and the diagnosis was confirmed at surgery. After surgery, he was discharged with no recurrent bleeding. This case highlights the importance of high suspicion and prompt management of tracheoinnominate artery fistula.